Achieving Open Defecation Free: Lessons from Rural Sanitation and Hygiene Success in Svay Rieng Province, Cambodia - Hak Keo; Mardy Serey; Polyva Toch; Borosh Chhim; Samnang Chhin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study documents Svay Rieng as Cambodia’s first Open Defecation Free province, offering a replicable model for others. It emphasizes effective coordination, implementation, and the Provincial Department of Rural Development’s technical role in advancing water, sanitation, and hygiene initiatives across Cambodia’s 25 provinces. Methodology: This study analyzes the multi-level coordination behind Svay Rieng’s Open Defecation Free achievement, focusing on collaboration among provincial departments, municipalities, communes, and local focal points. It documents planning, execution, and community engagement strategies, highlighting effective coordination mechanisms and implementation procedures that enabled the successful elimination of open defecation across the province. Main Findings: The study attributes Svay Rieng’s Open Defecation Free success to three key hygiene practices: toilet use, safe drinking water, and handwashing with soap. Strong coordination from provincial to village levels was vital. Local initiatives effectively aligned with national frameworks, including the National Strategic Plan (2014-2025), National Action Plan, and Provincial Action Plan II (2019-2023), ensuring cohesive planning and implementation. Novelty/Originality of this study: This study uniquely documents Cambodia’s first province-wide Open Defecation Free success, offering a pioneering, adaptable framework for rural sanitation. It highlights effective multi-stakeholder coordination and community engagement, aligning with national plans and local goals. The findings provide valuable insights for policymakers and practitioners in Cambodia and other developing countries pursuing sustainable sanitation solutions.